SAFETY OF ACE INHIBITORS IN CHILDREN WITH HEART FAILURE. Issue 1 (14th December 2015) - der Meulen, Marijke van; Läer, Stephanie; Castro, Cristina; Khalil, Feras; de Wildt, Saskia; Dalinghaus, Michiel; Jovanović, Ida; Bajčetić, Milica; Lagler, Florian
Abstract : Background: ACE inhibitors (ACE-I) are a cornerstone in the treatment of children with heart failure. Little is known on the pharmacokinetics (PK) and pharmacodynamics (PD) of enalapril in children. LENA trials will investigate a novel child-appropriate solid drug formulation of enalapril and obtain PK, PD and safety data. For this study clear safety cut-offs need to determined. Aim: To review the literature on safety of ACE-I in paediatric heart failure. Methods: We searched electronic databases and reference lists of relevant studies. Inclusion criteria were 1. Randomized Controlled Trials (RCT), Controlled trials (CT), case reports or retrospective cohorts. 2. Patients under 18 years with congestive heart failure. 3. Any kind of ACE-I 4. Outcome measures: Mortality, hypotension, renal failure, hyperkalaemia, liver enzyme rise, cough, neutropenia. Results: We assessed 12 of 593 articles as relevant: 2 RCTs, 5 CTs, 3 retrospective cohort studies and 2 case reports on a total of 734 children with heart failure. Systematic analyses was hampered by the heterogeneity of the study designs. In summary, we identified renal failure, hypotension and hyperkalemia as the most important side effects. Renal failure was found in 80 patients (11%), hypotension in 33 (4, 5%) and hyperkalemia in 5 (0, 7%). Five studies (n= 315 children) suggest that young age and low weight increases the risk of renal failure. Conclusions: Renal failure, hypotension and hyperkalemia are the most reported adverse events in children on an ACE-I for heart failure. We defined strict adjusting- and stopping rules for enalapril based on an Acute Kidney Injury scale, b. on values of systolic blood pressure and on c. serum levels potassium. The research leading to these results has received funding from the European Union Seventh Framework Programme (FP7/2007–2013) under grant agreement n°602295 (LENA).